Evolución de los depósitos y créditos de las cajas municipales de ahorro y crédito de la Región Loreto periodo 2017-2023 - Padilla Solís, Gimena Nicole (2024)
The general objective of this study was to analyze the evolution of the level of deposits and credits of the municipal savings banks of the Loreto region in a period of 7 years, from 2017 to 2023, using the quantitative methodology with a non-experimental design and a longitudinal design type and descriptive scope. Descriptive statistics were used to didactically explain the behavior of the independent variables, the research showed that the deposits had a fluctuating behavior, observing a not very differentiated increase in the level of deposits during the first 6 years of the study. In 2017 the level of deposits was S/2 268 383,98 billion soles, increasing in 2018 by 13,50%, 2019 by 9,18%, 2020 by 4,32%, 2021 by 1,37%, 2022 by 0,10%. However, in 2023 the level of deposits decreased by -1,58% establishing a total of S/. 3 014 963,83 billion soles in deposits. On the other hand, credits showed a constant increase during the study period, starting in 2017 with S/. 3 106 106,17 billion soles in credits, increasing in 2018 by 10,34%, in 2019 by 9,25%, in 2020 by 4,09%, in 2021 by 11,08%, in 2022 by 9,79% and finally in 2023 by 6,05% closing the credit level at S/. 5 282 316,74 billion soles. The study concluded that deposits and loans as a whole did not show a constant upward trend during the period 2017-2023.